2013
DOI: 10.1186/2042-6410-4-17
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the prognostic significance of KRAS codons 12 and 13, and BRAF mutations in colorectal cancer: a cohort study

Abstract: BackgroundActivating KRAS and BRAF mutations predict unresponsiveness to EGFR-targeting therapies in colorectal cancer (CRC), but their prognostic value needs further validation. In this study, we investigated the impact of KRAS codons 12 and 13, and BRAF mutations on survival from CRC, overall and stratified by sex, in a large prospective cohort study.MethodsKRAS codons 12 and 13, and BRAF mutations were analysed by pyrosequencing of tumours from 525 and 524 incident CRC cases in The Malmö Diet and Cancer Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 48 publications
5
21
0
Order By: Relevance
“…Of note, in the here examined cohort, it has recently been shown that mutation in KRAS codon 13, but not in codon 12, was associated with a significantly reduced cancer specific survival which is in line with other previous publications [16], [38], [39] [40], and most previous studies have not considered the prognostic value of specific mutations [7][9], [37], [41]. Furthermore, KRAS codon 13 mutation was found to be significantly associated with metastatic disease, and codon 12 mutation with mucinous tumour type, indicating that specific KRAS mutations have different impact on protein functionality, and hence influence clinical outcome in CRC patients differently [16].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Of note, in the here examined cohort, it has recently been shown that mutation in KRAS codon 13, but not in codon 12, was associated with a significantly reduced cancer specific survival which is in line with other previous publications [16], [38], [39] [40], and most previous studies have not considered the prognostic value of specific mutations [7][9], [37], [41]. Furthermore, KRAS codon 13 mutation was found to be significantly associated with metastatic disease, and codon 12 mutation with mucinous tumour type, indicating that specific KRAS mutations have different impact on protein functionality, and hence influence clinical outcome in CRC patients differently [16].…”
Section: Discussionsupporting
confidence: 93%
“…BRAF mutations are more frequent in women, in right-sided tumours and are more often associated with lower differentiation grade, mucinous histology and, subsequently, a poor prognosis [9], [11][16].…”
Section: Introductionmentioning
confidence: 99%
“…These findings were supported by two additional studies in 2009 and 2012 [255,256]. In contrast, Wangefjord and colleagues found that KRAS codon 13 mutations were associated with significantly reduced cancer specific survival in women, but not in men, although only in unadjusted analyses [257]. We recently confirmed these results on overall survival for women with stage III disease in a large population representative series of CRC (Merok et al, submitted manuscript).…”
Section: Prognostic Biomarkerssupporting
confidence: 65%
“…Furthermore, a study of 160 CRCs of varying tumor stages and treatments found that KRAS codon 13, but not codon 12, mutations were associated with higher S-phase fractions, increased nodal metastases, and adverse outcome compared to wild type (16). A Swedish population-based study of 525 CRCs reported that individuals with KRAS codon 13 (but not codon 12) mutations experienced shorter cancer-specific survival in unadjusted, but not adjusted, analysis (30). Limitations of prior studies include the inconsistent incorporation of patients with BRAF mutations (in the comparison group) and variable patient therapies, which can confound the interpretation of the KRAS prognostic data (31-33).…”
Section: Discussionmentioning
confidence: 99%